Sports Imaging of Team Handball Injuries - Fritz, Benjamin; Parkar, Anagha P.; Cerezal, Luis; Storgaard, Morten; Boesen, Mikael; Åström, Gunnar; Fritz, Jan (Seminars in Musculoskeletal Radiology, 2020)
Team handball is a fast high-scoring indoor contact sport with > 20 million registered players who are organized in > 150 federations worldwide. The combination of complex and unique biomechanics of handball throwing, permitted body tackles and blocks, and illegal fouls contribute to team handball ranging among the four athletic sports that carry the highest risks of injury. The categories include a broad range of acute and overuse injuries that most commonly occur in the shoulder, knee, and ankle. In concert with sports medicine, physicians, surgeons, physical therapists, and radiologists consult in the care of handball players through the appropriate use and expert interpretations of radiography, ultrasonography, CT, and MRI studies to facilitate diagnosis, characterization, and healing of a broad spectrum of acute, complex, concomitant, chronic, and overuse injuries. This article is based on published data and the author team's cumulative experience in playing and caring for handball players in Denmark, Sweden, Norway, Germany, Switzerland, and Spain. The article reviews and illustrates the spectrum of common handball injuries and highlights the contributions of sports imaging for diagnosis and management.
Keywords: handball; magnetic resonance imaging; computed tomography; radiography; ultrasonography